Art Therapy as a Means of Improving Mental Wellbeing of Housewives - Nailatus Syarifah; Syafira Rizka Ulya; Fara Okta Prastika; Eni Wulandari (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Mothers are very valuable figures, with an influence big in the family and society. Giving birth, nurturing, caring for, and educating children is an important role of the mother sacrifice and love. A mother's happiness is influential in producing a quality generation, because happy mothers can manage their emotions well, so that children grow optimally and are able to regulate their own emotions. This program aims to improve housewives' emotion regulation skills through art methods. Therapy, with the main objective of creating a family environment that is more harmonious and supportive of children's development. this practical and innovative approach, it is expected that mothers have a better ability to recognize, manage and overcoming negative emotions. The outcome of this program is published through mass media and national journals focusing on community service, in range of impact. Specific objectives of the program include enhancement of positive and harmonious relationships between families, especially children, through more interaction quality based on creativity and art. Inaddition, this program also aims to spread information about art therapy a tool effectivein addressing problems emotions society. Thus, this seminar is expected to provide significant support for housewives in manage their emotions, improving mental well-being, and create a home environment that is more conducive to optimal child growth.